PENGARUH NILAI PENGANTAR AKUNTANSI TERHADAP KEMAMPUAN MAHASISWA MEMAHAMI KOMPUTER AKUNTANSI PADA PROGRAM STUDI PERBANKAN DAN KEUANGAN POLITEKNIK NEGERI MEDAN - Jantianus, Jantianus; Khairul, Khairul (STMIK Budi Darma, 2018)
Ease of understanding Accounting Computers in principle is influenced by mastery of Introduction to Accounting in a systematic manner, assuming that it is capable of operating computers properly. To find out the magnitude of the influence in this study taken a sample of introductory Accounting values from a number of first semester 2017 students and the same data sample for students of Computer Accounting (Accurate) courses when they are in the fourth semester 2018. Feasibility until the data is tested by the normality test to find out the distribution of data and by linearity test to obtain linear functions. The data that has been obtained and tested for its feasibility is processed by Linear Regression using SPSS 24. From the results of the research that has been done obtained a regression equation: Y = 67,953 0.35X, which describes each increase in the value of introductory Accounting one unit will affect 0.35 to Computer Accounting value, but in testing the hypothesis that the value of Introduction to Accounting obtained by students does not affect their ability to obtain Computer Accounting values, one of the causes of this is due to the lack of skills of students to operate computers.Keywords: influence, value, ability